Climate change: Hungary’s perception and how we adopt renewables against it - Lénárt, Viktor Márk (Acta Geographica Debrecina Landscape & Environment series, 2023)
The aim of the research is to present the effects of climate change in Hungary, the public opinion on climate change and the related social acceptance of renewable energy sources and the reasons for their adaptation. Previous surveys have shown that the Hungarian population is aware of the dangers of climate change, yet they are less willing to act against either climate change or pollution. Global climate change threatens peripheral regions more than central regions, as several studies have shown. Hungary has so far successfully met its climate targets but is still far from reaching the 2050 climate neutrality target. The financial and economic situation of the Hungarian population does not currently allow them to widely adopt the opportunities offered by renewable energy sources, but those who can afford to invest in the technologies do so primarily for the financial savings, not to fight climate change.